The Influence of Transparency, Accountability, and Service Quality on the Trust of "Muzakki" (A Case Study at the Lazismu Office in Grobogan Regency) - Triana Nur Cahyani; Fariha Azzahra (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2025)
Background: Indonesia is referred to as the fourth-largest Muslim-majority country in the world, with 86.19% of its population being Muslim (BPS, 2020). In Islamic terminology, "Muzakki" refers to individuals who pay zakat, while the recipients are called "Mustahiq." In companies, whether for-profit or non-profit, strategies are required to maintain their existence and compete with others. One such strategy involves implementing structured corporate governance practices, including transparency in fund management and accountability. Additionally, service quality is the most important strategy, serving as a benchmark for a company’s future success. Purpose: This study aims to examine and articulate how transparency, accountability, and service quality influence the trust of "Muzakki," considering the context and the identified issues. Method: This study used a quantitative approach by conducting observations and distributing questionnaires to zakat donors, or "Muzakki," in the Grobogan Regency. The "Muzakki" population consisted of 420 individuals, and a purposive sampling technique was employed, resulting in 150 samples. The criteria for participants were being at least 17 years old and solely paying zakat. Data analysis was conducted with the aid of SmartPLS 4 software. Results: The results show that transparency has a significant positive effect on the trust of "Muzakki" in the Lazismu office in Grobogan Regency. Accountability does not have a significant effect on the trust of "Muzakki" in the Lazismu office, while service quality has a significant positive effect on their trust. Conclusion It is recommended that the Lazismu office in Grobogan Regency further improve accountability in fund management to enhance the trust of zakat donors, or "Muzakki," while maintaining and improving transparency in fund management and service quality for better outcomes in the future. Suggestion: For future research, other factors influencing trust can be explored, and intervening variables such as organizational reputation, personal experience of "muzakki", and others can be added. Keywords: Transparency, Accountability, Service Quality, Trust